DIVERSIFICATION OF THE PEASANTS’ RATIONALITY AS STREET VENDORS IN JUNREJO, BATU CITY - Rosyidin, Aditya Danan (University of Muhammadiyah Malang, 2019)
In the range of 2009 to 2013, agricultural production in Batu City declined. The impact of this decline in agriculture has made farm labor economically difficult. This makes the farm laborers begin to abandon their fighting activities. This phenomenon makes the diversification of the rationality of the work of farm labors into street vendors. The purpose of this study was to describe the scheme of voluntaristic action of farm laborers in achieving their economic needs in the street vendor sector, as well as to describe the rationality of the diversification of farm laborers? jobs into street vendors in the Junrejo District of Batu City. This study uses a qualitative approach with descriptive type. The subjects of the study were farm laborers who chose to leave work as farm laborers to turn into street vendors and farm laborers who still remained farm laborers but also worked as street vendors. The technique of collecting data uses observation, interviews, and documentation, while the data analysis technique uses data reduction, data categorization, synthesis. The technique of checking the validity of the data uses persistent observation, triangulation, and peerderieting. The results of this study are that the scheme of voluntaristic action of farm laborers in achieving their economic needs in the street vendors sector starts from the rapid tourism in Batu City. Farm workers have actions towards sluggish agriculture by utilizing the development of tourism in Batu City. Some of their actions were to become street vendors in the Batu City Square area, open another business and become an online driver. One of the rational actions of farm workers is to diversify work. Farmers in diversifying their work are based on consideration of the work of farm labors who are very heavy and have little income. The aim of farm workers in diversifying their work is to obtain greater profits compared to the work of farm workers.